Living with Hereditary Haemorrhagic Telangiectasia: stigma, coping with unpredictable symptoms, and self-advocacy. Issue 10 (3rd October 2019) - Sexton, Adrienne; Gargan, Bridget; Taylor, Jessica; Bogwitz, Michael; Winship, Ingrid
Abstract: Objective: Hereditary Haemorrhagic Telangiectasia (HHT) is a genetic condition causing frequent nose bleeds, skin lesions (telangiectasia) and arteriovenous malformations. Approximately, 50% of people experience life-threatening HHT symptoms including haemorrhages in the brain, lungs and liver. This study aimed to gain a qualitative understanding of the psychosocial impact of HHT over time.Design : Using a phenomenological framework, a rigorous narrative analysis was performed on 20 semi-structured interviews with individuals with HHT aged 20s–60s.Main outcome measures: Qualitative themes explaining life experiences prior to and following a clinical diagnosis of HHT.Results: Narratives highlighted four psychosocial themes: (i) the psychological impact of visible symptoms was significant and related to experiences of social stigma, (ii) individuals struggled to identify triggers of symptoms in order to reduce unpredictability, (iii) an illness identity was rejected by minimising HHT when talking about the present self, and by positive reframing as 'lucky' and (iv) self-advocacy was necessitated due to lack of expert coordinated care.Conclusion: HHT has a demanding impact on social, physical and psychological well-being. These findings have significant implications for health care, as narratives about interactions with health professionals often used the terms 'frustrating' and 'not being heard'.